PERTUMBUHAN DAN SIFAT MEKANIKA KAYU JATI (Tectona grandis L.f) UMUR 20 TAHUN DI KOTA KENDARI DAN KABUPATEN KONAWE SELATAN - Niken Pujirahayu; Aminuddin Mane Kandari; Abigael Kabe; Muhammad Syaiten Alfaruq (Halu Oleo University, 2022)
ABSTRACTThis study aims to determine the growth and mechanical properties of 20-year-old teak growing in Kendari City and South Konawe. This research was conducted at the Laboratory of Utilization and Processing of Forest Products, Faculty of Forestry, Hasanuddin University, Makassar, South Sulawesi. Tree diameter was used as a wood growth variable. The method of testing the mechanical properties of wood is carried out according to ASTM: D143–94 with the variable compressive strength parallel to the fiber, MOR, and MOE. The results showed that the diameter of the 20-year-old teak from Konawe Selatan was 22.79 cm higher than Kendari teak, which was 22.39 cm. The mechanical properties of 20-year-old teak wood at the base are higher than the middle and the top of South Konawe and Kendari teak. The compressive strength parallels to fiber, MOR, and MOE values of teak from South Konawe were higher than in Kendari City. The average compressive strength parallel to the South Konawe fiber is 477.01 kg cm-2, and the Kendari city is 457.58 kg cm-2. The average value of MOR for South Konawe teak is 932.51 kg cm-2, and Kendari City is 872.08 kg cm-2. The average MOE value for South Konawe teak is 85.860.48 kg cm-2, and Kendari City is 78.677.89 kg cm-2.